If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(7f + 1) = 0 Reorder the terms: 8(1 + 7f) = 0 (1 * 8 + 7f * 8) = 0 (8 + 56f) = 0 Solving 8 + 56f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 56f = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 56f = 0 + -8 56f = 0 + -8 Combine like terms: 0 + -8 = -8 56f = -8 Divide each side by '56'. f = -0.1428571429 Simplifying f = -0.1428571429
| (65/360)*18 | | 5x+4=x-2+3x+7 | | Q=5p-5 | | 6y-10=3y-7 | | 5x+4=80 | | x-2+3x+7=80 | | 95-x=30 | | F(x)=x^2(108-4x) | | x^2+y^2-10x+6y=15 | | 9=y^2-5 | | 26(y^2-5y+6)=0 | | (4k+5)(k+1)=1 | | 13x+17=6x+66 | | y=3+sqrt(y^2-5) | | 12x+6=5x+76 | | -x+12=3x-12 | | -8x-7=-5x-13 | | .5x+12.3=7.1-1.1 | | 3x+21=2x+17 | | 4x^3+22=7 | | -5x+12=-x+32 | | -3x+6=-2x+7 | | -5x+15=-4x+12 | | 3x-14=6x-38 | | 28-(-3)*(-7)= | | 37.5=x^3 | | 5x-6=-x+6 | | 22x+4+35x+5=180 | | 1-x^2=-7-3 | | (x-3/4)^2 | | 2x+23+2x+23=8x | | 4.5*X=13.5 |